Total Ankle Replacement for Treatment of End-Stage Osteoarthritis in Elderly Patients - Beat Hintermann; Markus Knupp; Lukas Zwicky; Alexej Barg (Journal of Aging Research)
End-stage osteoarthritis of the ankle is a disabling problem, particularly in elderly patients who experience an overall loss of mobility and functional impairment and who then need compensatory adaption. Ankle arthrodesis, which has been demonstrated to provide postoperative pain relief and hindfoot stability, leaves the patient with a stiff foot and gait changes. For elderly patient, these changes may be more critical than generally believed. Additionally, the long duration of healing and rehabilitation process needed for ankle arthrodesis may be problematic in the elderly. In contrast to ankle arthrodesis, total ankle replacement has significant advantages including a less strenuous postoperative rehabilitation and preservation of ankle motion which supports physiological gait. Recently, total ankle replacement has evolved as a safe surgical treatment in patients with end-stage ankle osteoarthritis with reliable mid- to long-term results. Total ankle replacement needs less immobilization than arthrodesis and does allow for early weight-bearing and should be considered as a treatment option of first choice in many elderly patients with end-stage osteoarthritis of the ankle, especially in elderly patients with lower expectations and physical demands.